Majlis Anugerah Kelab Persatuan Pelajar 2022 / Melati Desa - Desa, Melati (Academy of Language Studies, 2022)
The Students Development Programme is one of the institutional initiatives in helping to build students’ confidence indirectly. There is no denying that there are a handful of divinely endowed students who naturally possess talents in leadership. Such individuals need minimal monitoring in order to prepare themselves to face the world out there. Therefore, the emphasis is on the institutional efforts in shaping and producing competitive human beings not only at the university level but also globally. Thus, on 27 January 2022, the Student Affairs Department (BHEP) of UiTMCPP organised the Ceremonie d’appreciation du Club Etudiant 2022 which aimed at celebrating individuals who successfully carry out club activities throughout the past two years in 2020 and 2021. According to BHEP records, there are currently 98 club associations registered under UiTMCPP. However, at the time of the ceremony, only 45 club associations were categorised as active. This means that only 45.9% of the registered clubs or societies were actively engaged in conducting student activities during the recent Covid-19 pandemic. Nevertheless, the Awards Ceremony was still being held to recognise the individuals as well as clubs that were deemed outstanding. As we all know, the years 2020 and 2021 were the most challenging years because the world was hit by the Corona-19 pandemic which led to a change to the virtual environment and online learning and interactions. Yet, both the Japanese Language Club (JLC) and the English Language Club (ELC) still ensured that their members were actively united virtually.